JENIS KOMUNIKASI YANG DILAKUKAN DA’I DALAM MENYAMPAIKAN PESAN ISLAM KEPADA MASYARAKAT PEDALAMAN - Jamaluddin Iskandar (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2021)
Communication is the process of delivering information about Islam by a Muslim communicator to the recipient to achieve a certain goal that is in line with what is outlined in the Qur'an and al-Sunnah. This study aims to see how the communication patterns of da'i in conveying Islamic messages to rural communities. This qualitative research uses a case study design. Data collection for this study involved eight research participants and also informants, while the semi-structured interview method was used as the research instrument. The subjects of the research were preachers who were directly involved in da'wah to the community in Maseo Village, Pipikoro District, Sigi Regency. Purposive sampling is used in the research sampling process. Research findings show that the communication pattern of da'wah to rural communities involves three main stages, namely the initiation stage, strategy, and conversation topics during communication. Each element has its role and influence that can affect the work of the da'i. For preachers who are proactive and can carry out various skills according to the current situation, communication with the community can lead to something positive and close to them in the village is welcomed by the community.